Light‐Controlled Radical Polymerization of Functional Methacrylates Prepared by Enzymatic Transacylation. Issue 1 (4th December 2015) - Mommer, Stefan; Köhler, Jens; Keul, Helmut; Möller, Martin
Abstract : Well‐defined homo and block copolymers are prepared with methyl methacrylate, pentyl methacrylate, 3‐phenylpropyl methacrylate, and 6‐thiobenzoylhexyl methacrylate using Ir(ppy)3 as a catalyst. It is shown that the advantages of the light‐controlled radical polymerization can be exploited also for these special monomers as prepared by enzymatic transacylation without time‐consuming labor‐intensive removal of side products. Furthermore, it is shown that the polymerization is significantly affected even by small variations in the irradiation and therefore also by choice of the light source. In contrast to our recent report we therefore recommend removal of the heterogeneous supported enzyme by filtration before polymerization. Because of the sensitivity of the polymerization process to the irradiation, turbidity caused by the bead‐supported enzyme can affect the reproducibility of the polymer preparation. Results obtained with methyl methacrylate as monomer could only be transferred to the above‐mentioned functional monomers by proper choice of the light source. On the basis of kinetic investigations, the effect of the irradiation source, the catalyst concentration, and the alcohol residue on the methacrylate used are discussed. Finally, the optimized experimental conditions are applied for the preparation of different block copolymers. Abstract : Monomer synthesis by enzyme‐catalyzed transacylation combined with light‐controlled Iridium(III)‐catalyzed radical polymerization is used for block copolymer syntheses. The influence of the light source, catalyst concentration, and reactivity of the functional monomers on the efficiency of block copolymer synthesis is investigated.